KEMAMPUAN SISWA KELAS XI SMA NEGERI 13 OKU DALAM MENULIS RESENSI NOVEL DIA ADALAH KAKAKKU KARYA TERE LIYE - Aryanti Agustina; Erwanto Erwanto (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
The purpose of this study is (1) to describe the ability of class XI students to write a novel review "He is my brother" by Tere Liye, (2) to determine the factors that influence the difficulties of class XI students in writing novel reviews. The type of research used is descriptive qualitative research. The method used is descriptive method with data collection techniques in the form of written tests and questionnaires. From the results of the study, students who scored 80-10 were 2 people (8.69%) in the "Very Good" category, students who scored 66-79 were 10 people (43.47%) with "Good Category", students 11 people (47.82%) scored 56-65 in the "Enough" category. Furthermore, based on the analysis of the questionnaire data, it is known that the factors that influence the difficulty of students writing novel reviews are (1) there are still many students who are not interested in taking novel review writing lessons, (2) students are quite difficult to describe in the title, book data, introduction, body. proper reviews and closings, (3) students still need a lot of examples of review material to make it easier to write novel reviews, (4) students do not often write novel reviews apart from the assignments given by the teacher at school.